THE EFFECTS OF ANTIDEPRESSANT DRUGS ON POLYMORPHONUCLEAR LEUKOCYTE FUNCTIONS AND LEVELS OF FOLIC ACID, VITAMIN B-12, ZINC AND COPPER IN MAJOR DEPRESSION - (:unkn) unknown (NOBEL ILAC, 2013)
Objective: Today it is known that frequently used antineoplastic agents, analgesics and antibiotics affect the immune system cells and can modify polymorphonuclear leukocyte (PMN) functions such as phagocytosis, lymphocyte proliferation and production of various cytokines. In this study we investigated the effect of antidepresssant drugs on PMN functions, serum folic acid, vitamin B-12, zinc, copper levels and hematological parameters in the patients with major depression (MD). Material and Method: PMNs were isolated by Ficoll-Hypaque gradient centrifugation method. Phagocytosis and intracellular killing activity were assayed by modifying Alexander's method. Serum folic acid, vitamin B-12, copper and hematology parameters were detected with the biochemical analyzer. Serum zinc levels were measured by flame atomic absorption spectrometer BEL Results: White blood cell (WBC), neutrophil counts (NE) significantly increased after 2 months of antidepressant drug treatment (p<0.05). The phagocytic activity of PMN of MD patients was found same as healthy volunteers, the intracellular killing activity was found lower than that of healthy volunteers. The PMN's phagocytic activity after one and two months of antidepressant drug treatment insignificantly increased and the intracellular killing activity also insignificantly increased after one month of treatment when compared with those before treatment. The results were not found statistically significant. Serum folic acid, vitamin B-12, zinc and copper levels were found in reference value intervals compared to those before treatment. Conclusions: This study showed that WBC, NE counts in patients with MD significantly increased in the reference value intervals after antidepressant drug treatment (p<0.05). We conclude that antidepressant drugs have not deleterious effects on PMN functions, serum folic acid, vitamin B-12, zinc, copper levels of patients with MD.
Keywords: Antidepressant drugs; phagocytosis; folic acid; vitamin B-12; zinc; copper; INTERFERON-GAMMA; IMMUNE-SYSTEM; SERUM